Border Rhetorics : Citizenship and Identity on the US-Mexico Frontier - DeChaine, D. Robert (Daniel Robert), 1961- (Book collections on Project MUSE., 2012)
Border Rhetorics is a collection of essays that undertakes a wide-ranging examination of the US-Mexico border as it functions in the rhetorical production of civic unity in the United States. A "border" is a powerful and versatile concept, variously invoked as the delineation of geographical territories, as a judicial marker of citizenship, and as an ideological trope for defining inclusion and exclusion. It has implications for both the empowerment and subjugation of any given populace. Both real and imagined, the border separates a zone of physical and symbolic exchange